Duckman : private dick/family man. The complete series [videorecording (DVD)] - Peck, Everett; Osborn, Ron; Reno, Jeff; Csupo, Gabor; Klasky, Arlene (CBS DVD : Paramount Pictures, 2018)
"He's crude. He's rude. He's lewd. Yes, he's the total dick: Duckman the slovenly, smart-mouted, prviate eye ladies don't like and men don't want to be like. Together with Cornfed, his portly porcine partner in crime solving, this defective detective amazingly manages to solve crimes and be a single parent to his hilariously dysfunctional sons at the same time"--Container